Determination of Rare Earth Elements in Orchards Soil by Inductively Coupled Plasma-Atomic Emission Spectroscopy - Xue, Jun; Zhong, Lin-Sheng; Fan, Yu-Lan; Li, Xun (Asian Journal of Chemistry, 2012)
To investigate spectral interference of La, Ce, Nd, Sm, Eu, Gd, Tb, Yb, Lu and Y when detecting by inductively coupled plasma-atomic emission spectroscopy (ICP-AES), different types of soils were digested with a mixture of HF + HNO3 + HCl by microwave digestion instrument and precipitated twice to remove most of the matrix elements. The results showed a good method with high sensitivity, strong antiinterference ability to determine these elements simultaneously. The results to detect the soil standard reference materials (GSS-4, GSS-5) showed that measured values are all in range the standard value allowed and consistent with the standard value, indicating that the method is accurate and reliable. The detection limit of each element range from 0.2-38.2 μg L-1, the relative standard deviations were between 0.8 and 3.2 %. This method has been successfully applied to determine the content of rare earth elements in soil samples from orchards in southern Jiangxi and the distribution of rare earth elements in the different types of soil were explored.